Senegal's saline soils have a future - despite the drought - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Saloum, Gambia, Casamance and Senegal estuaries are set in the midst of vast, desolate stretches of land where only a few wizened trees and clumps of dry and yellowing grass survive. These are the tannest It seems impossible to think that these...